Diagnosis of fetal non‐chromosomal abnormalities on routine ultrasound examination at 11–13 weeks' gestation. (4th October 2019) - Syngelaki, A.; Hammami, A.; Bower, S.; Zidere, V.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the performance of the routine 11–13‐week scan in detecting fetal non‐chromosomal abnormalities. Methods: This was a retrospective study of prospectively collected data from 100 997 singleton pregnancies attending for a routine ultrasound examination of fetal anatomy, performed according to a standardized protocol, at 11–13 weeks' gestation. All continuing pregnancies had an additional scan at 18–24 weeks and 71 754 had a scan at either 30–34 or 35–37 weeks. The final diagnosis of fetal abnormality was based on the results of postnatal examination in cases of live birth and on the findings of the last ultrasound examination in cases of pregnancy termination, miscarriage or stillbirth. The performance of the 11–13‐week scan in the detection of fetal abnormalities was determined. Results: The study population contained 1720 (1.7%) pregnancies with a fetal abnormality, including 474 (27.6%) detected on the first‐trimester scan, 926 (53.8%) detected on the second‐trimester scan and 320 (18.6%) detected in the third trimester or postnatally. At 11–13 weeks' gestation, we diagnosed all cases of acrania, alobar holoprosencephaly, encephalocele, tricuspid or pulmonary atresia, pentalogy of Cantrell, ectopia cordis, exomphalos, gastroschisis and body‐stalk anomaly and > 50% of cases of open spina bifida, hypoplastic left heart syndrome, atrioventricular septal defect, complex heart defect, left atrial isomerism (interrupted inferior vena cava with normal intracardiac anatomy), lower urinary tract obstruction, absence of extremities, fetal akinesia deformation sequence and lethal skeletal dysplasia. Common abnormalities that were detected in < 10% of cases at 11–13 weeks included ventriculomegaly, agenesis of the corpus callosum, isolated cleft lip, congenital pulmonary airway malformation, ventricular septal defect, abdominal cysts, unilateral renal agenesis or multicystic kidney, hydronephrosis, duplex kidney, hypospadias and talipes. Conclusions: A routine 11–13‐week scan, carried out according to a standardized protocol, can identify many severe non‐chromosomal fetal abnormalities. A summary statistic of the performance of the first‐trimester scan is futile because some abnormalities are always detectable, whereas others are either non‐detectable or sometimes detectable. To maximize prenatal detection of abnormalities, additional scans in both the second and third trimesters are necessary. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. RESUMEN: Diagnóstico de anomalías fetales no cromosómicas en la ecografía de rutina a las 11–13 semanas de gestación Objetivo: Examinar el desempeño de la ecografía de rutina a las 11–13 semanas en la detección de anomalías fetales no cromosómicas. Métodos: Esta investigación fue un estudio retrospectivo de datos recogidos prospectivamente de 100 997 embarazos con feto único que acudieron a un examen ecográfico de rutina de la anatomía fetal, realizado de acuerdo con un protocolo estandarizado, a las 11–13 semanas de gestación. Todos los embarazos que continuaron se sometieron a una exploración adicional a las 18‐24 semanas y 71754 se sometieron a una exploración a las 30‐34 o a las 35‐37 semanas. El diagnóstico final de la anomalía fetal se basó en los resultados del examen postnatal en los casos de nacimientos vivos y en los hallazgos del último examen ecográfico en los casos de interrupción del embarazo, aborto o éxitus fetal. Se determinó el rendimiento de la exploración de las 11–13 semanas en la detección de anomalías fetales. Resultados: La población del estudio contenía 1720 (1, 7%) embarazos con una anormalidad fetal, entre ellos 474 (27, 6%) detectados en la exploración del primer trimestre, 926 (53, 8%) detectados en la del segundo trimestre y 320 (18, 6%) detectados en el tercer trimestre o postnatalmente. A las 11‐13 semanas de gestación, se diagnosticaron todos los casos de acrania, holoprosencefalia alobar, encefalocele, atresia tricúspide o pulmonar, pentalogía de Cantrell, ectopia cordis, onfalocele, gastrosquisis y anomalía del pedículo embrionario y >50% de los casos de espina bífida abierta, síndrome del hemicardio izquierdo hipoplásico, comunicación auriculoventricular, defecto cardíaco complejo, isomerismo de la aurícula izquierda (vena cava inferior interrumpida con anatomía intracardíaca normal), obstrucción del tracto urinario inferior, ausencia de extremidades, secuencia de deformación de la acinesia fetal y displasia esquelética letal. Las anomalías comunes que se detectaron en <10% de los casos a las 11–13 semanas incluyeron ventriculomegalia, agenesia del cuerpo calloso, labio leporino aislado, malformación congénita de las vías respiratorias pulmonares, comunicación interventricular, quistes abdominales, agenesia renal unilateral o riñón multiquístico, hidronefrosis, duplicidad renal, hipospadias y pie zambo. Conclusión: Una exploración rutinaria a las 11–13 semanas, realizada de acuerdo con un protocolo estandarizado, puede identificar muchas anomalías fetales no cromosómicas graves. Un resumen estadístico del desempeño de la exploración del primer trimestre es inútil porque algunas anomalías son siempre detectables, mientras que otras no lo son o solo lo son a veces. Para maximizar la detección prenatal de anormalidades, se necesitan exploraciones adicionales tanto en el segundo como en el tercer trimestre. 摘要: 妊娠11‐13周常规超声检查胎儿非染色体异常的诊断 目标: 针对常规的11‐13周胎儿非染色体异常扫描检测，审视相关表现。 方法: 这是一项回顾性研究，前瞻性收集了100 997例单胎妊娠数据。这些单胎妊娠孕妇在妊娠11‐13周时，按照标准化方案接受了胎儿解剖的常规超声检查。全体持续妊娠孕妇在18‐24周接受了额外的扫描，71 754例孕妇在30‐34周或35‐37周接受了一次扫描。胎儿异常的最终诊断基于产后检查结果(若为活产婴儿)，或上次超声检查结果(若为终止妊娠、流产或死产)。11‐13周扫描在胎儿异常诊断中的表现有了结论。 结果: 研究人群中有1720(1.7%)例胎儿异常妊娠病例，包括孕早期扫描时发现的474 (27.6%)例、孕中期扫描时发现的926 (53.8%)例、以及妊娠晚期或产后发现的320 (18.6%)例。妊娠11‐13周时发现所有受试者都患有肢端、前脑无裂、脑膨出、三尖瓣或肺动脉闭锁、五角肌、心脏异位、外淋巴结、腹裂和体柄异常，发现50%以上的受试者患有开放性脊柱裂、左心发育不全综合征、房室间隔缺损、复合性心脏缺损、左房异构(心内解剖正常的下腔静脉中断)、下尿路梗阻、四肢缺失、胎儿畸形序列及致死性骨骼发育不良。妊娠11‐13周在不足10%的受试者中发现的常见异常包括脑室扩大、胼胝体发育不全、孤立性唇裂、先天性肺气道畸形、室间隔缺损、腹腔囊肿、单侧肾发育不全或多囊肾、肾积水、双肾、尿道下裂和足内翻。 结论: 根据标准化方案进行的11‐13周常规扫描，可以发现许多严重的非染色体胎儿异常。对孕早期扫描结果进行汇总统计是徒劳无益的，因为有些异常在任何情况下都可以检测出来，其他异常则无法检测(但有时又可以检测)。为尽量发现产前异常，有必要进行额外的孕中期和妊娠晚期扫描。